Testing Genetic and Environmental Associations Between Personality Disorders and Cocaine Use: A Population-Based Twin Study. (25th January 2018) - Gillespie, Nathan A.; Aggen, Steven H.; Gentry, Amanda E.; Neale, Michael C.; Knudsen, Gun P.; Krueger, Robert F.; South, Susan C.; Czajkowski, Nikolai; Nesvåg, Ragnar; Ystrom, Eivind; Rosenström, Tom H.; Torvik, Fartein A.; et al.
Abstract : Until now, data have not been available to elucidate the genetic and environmental sources of comorbidity between all 10 DSM-IV personality disorders (PDs) and cocaine use. Our aim was to determine which PD traits are linked phenotypically and genetically to cocaine use. Cross-sectional data were obtained in a face-to-face interview between 1999 and 2004. Subjects were 1, 419 twins (µage = 28.2 years, range = 19–36) from the Norwegian Institute of Public Health Twin Panel, with complete lifetime cocaine use and criteria for all 10 DSM-IV PDs. Stepwise multiple and Least Absolute Shrinkage and Selection Operator (LASSO) regressions were used to identify PDs related to cocaine use. Twin models were fitted to estimate genetic and environmental associations between the PD traits and cocaine use. In the multiple regression, antisocial ( OR = 4.24, 95% CI [2.66, 6.86]) and borderline ( OR = 2.19, 95% CI [1.35, 3.57]) PD traits were significant predictors of cocaine use. In the LASSO regression, antisocial, borderline, and histrionic were significant predictors of cocaine use. Antisocial and borderline PD traits each explained 72% and 25% of the total genetic risks in cocaine use, respectively. Genetic risks in histrionic PD were not significantly related to cocaine use. Importantly, after removing criteria referencing substance use, antisocial PD explained 65% of the total genetic variance in cocaine use, whereas borderline explained only 4%. Among PD traits, antisocial is the strongest correlate of cocaine use, for which the association is driven largely by common genetic risks.